2016
DOI: 10.4174/astr.2016.91.5.239
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of clinically significant retained common bile duct stones after laparoscopic cholecystectomy for symptomatic cholelithiasis

Abstract: PurposeTo investigate the prevalence and clinical features of retained symptomatic common bile duct (CBD) stone detected after laparoscopic cholecystectomy (LC) in patients without preoperative evidence of CBD or intrahepatic duct stones.MethodsOf 2,111 patients who underwent cholecystectomy between September 2007 and December 2014 at Seoul Metropolitan Government-Seoul National University Boramae Medical Center, 1,467 underwent laparoscopic cholecystectomy for symptomatic gallbladder stones and their medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Some studies have suggested that the most cost-effective treatment strategy for most patients with symptomatic cholelithiasis involved laparoscopic cholecystectomy with routine IOC, as IOC could help surgeon to visualize the biliary anatomy and detect unexpected CBD stones [1819]. However, it remains debated whether IOC provides sufficient benefits in terms of its efficacy and safety to justify its routine application [1620]. In this study, there were no cases of IOC procedure to prevent bile duct injury in LSGB patient who underwent laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the most cost-effective treatment strategy for most patients with symptomatic cholelithiasis involved laparoscopic cholecystectomy with routine IOC, as IOC could help surgeon to visualize the biliary anatomy and detect unexpected CBD stones [1819]. However, it remains debated whether IOC provides sufficient benefits in terms of its efficacy and safety to justify its routine application [1620]. In this study, there were no cases of IOC procedure to prevent bile duct injury in LSGB patient who underwent laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Among the ADPKD cases, gallstones and prior cholecystectomy were identified as risk factors for first cholangitis episode. The identification of prior cholecystectomy as a risk factor for cholangitis was unexpected and possibly explained by a residual risk of cholangitis in gallstone formers following cholecystectomy (due to retained common bile duct gallstones, the prevalence of which has been estimated at 1.8% in a Korean population who had cholecystectomy performed for symptomatic cholelithiasis 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The median quality score for the RCTs was judged based on the Cochrane Handbook 13 . The quality assessment stratifies the current evidence and projects the need for further research on the topic based on the quality of the available evidence into: high-quality evidence where further research is not expected to change the current confidence in the estimate of the effect size, moderate-quality evidence if further research is likely to influence confidence in the estimated effect and may change it; low-quality evidence if further research is very likely to influence confidence in the estimate of Reference Design n-RCT Phillips et al 36 Gigot et al 31 Millat et al 34 Arvidsson et al 20 Berthou et al 29 DePaula et al 27 Martin et al 33 Lauter and Froines 24 Michel et al 25 Tokumura et al 40 Waage et al 42 Topal et al 41 Jameel et al 22 Tan et al 39 Santo et al 38 Dimov et al 26 Darrien et al 21 Mohamed et al 35 Zhang et al 19 Aawsaj et al 28 Rhodes et al 37 Cuschieri et al 30 Grubnik et al 32 Overall n-RCT heterogeneity: I 2 = 68%, P < 0·05 RCT heterogeneity: I 2 = 72% P < 0·05 Heterogeneity: 2 Forest plot for successful duct clearance in patients with choledocholithiasis undergoing a laparoscopic transcystic or transcholedochal approach. Studies that had 100 per cent success in both arms 18,23 were not included in the analysis, so calculation of an odds ratio was not possible in the pooled analysis.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Concomitant common bile duct (CBD) stones are present in 3–15 per cent of patients with symptomatic cholelithiasis in the Western world. In approximately 2 per cent of patients these stones are considered clinically significant. These patients require CBD stone extraction for symptomatic relief and to prevent serious associated complications, including cholangitis, hepatic abscess and acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%